The Enemy of My Enemy is My Friend: Adults Derive Arbitrary Sameness Relations through Trained Opposition. - Sbrocco, Guilherme; Harte, Colin; de Rose, Julio C. (Psychological Record, 2025)
Sidman's findings established equivalence relations as central to the behavioral analysis of language and cognition. Subsequent research dealt with other types of relations, such as difference, opposition, comparison, etc. However, some authors argue that evidence interpreted as the product of opposition relations can be explained only with equivalence, nonequivalence, and exclusion. The current study sought to produce derived sameness relations by training opposition relations. The experiment was designed so that the derived sameness relations would only be possible from double opposition relations. A training version of the implicit relational assessment procedure (IRAP) was used to train two linear series of opposite relations: A1-B2-C1-D2-E1 and A2-B1-C2-D1-E2, where B2 and B1 were the words happiness and sadness, respectively. It was expected that a stimulus opposite, for example, to the word happiness, would become coordinated to the word sadness. The primary research question involved assessing whether a double opposition (for example, A1-B2-Opposite and B2-C1-Opposite) would generate a derived relation of coordination (A1-C1-Same). Derived relations were verified using an appropriate derived relations test (for AC/CA and CE/EC) and a variation of a yes/no procedure (for AD and AE). Transformation of stimulus function was assessed using a Likert Scale. Results suggest the derivation of sameness relations by training opposition relations and an alternation between "Opposite" and "Same" along the linear series of opposite relations. Appropriate transformations of stimulus function were also observed. The present study provided data that cannot be interpreted relying solely on equivalence, nonequivalence, and exclusion.